Reconstructing and Reorganizing Experience: Weaving a Living Philosophy. Issue 6 (June 2021) - Rodgers, Carol; Anderson, Marti; Burkett, Beverley; Conley, Sean; Stanley, Claire; Turpin, Leslie
Background/Context: This study contributes to ongoing work in professional learning communities, self-study, and reflection. It offers a structure and a process rooted in a philosophy of practice grounded in various thinkers like Dewey, Rogers, Curran, Freire, Gattegno, Greene, and Carini. Purpose/Objective: The purpose of this study is to explore the process of one teacher educator inquiry group that has lasted nearly 30 years, and which has sought to enact Dewey's notion of education, "that reconstruction or reorganization of experience that adds meaning to experience and increases ability to direct the course of subsequent experience." Research Design: Our research design mirrors the reflective inquiry process of our group, that is, how we researched is simultaneously what we researched. The process itself follows a structure for reflection outlined by Dewey in Rodgers. It begins with recollected experiences, descriptions of those experiences, and is followed by a "harvesting of themes, " through analysis and interpretation, to possible modes of "intelligent action." The process is iterative and continuous. Conclusions: Our conclusions go beyond mere descriptions of our process. We come to the realization that, as Greene writes, being "wide-awake" to the particularities of our lives and work; to live intentionally, deliberately, and morally; and to be aware of who and why we are, and are to each other, is essential to a democratic society.